A Review of the Impact of Occupational Contact Dermatitis on Quality of Life. (16th March 2011) - Lau, Melisa Yi Zhi; Burgess, John Anthony; Nixon, Rosemary; Dharmage, Shyamali C.; Matheson, Melanie Claire
Abstract : Occupational contact dermatitis (OCD) is the most common occupational skin disease in many countries. We reviewed the current evidence on how OCD impacts on quality of life (QoL). The three commonly used QoL questionnaires in OCD were the Short-Form Health Survey (SF-36), the Dermatology Life Quality Index (DLQI), and the Skindex. Despite the availability of a variety of validated QoL instruments, none of them is specific to OCD or entirely adequate in capturing the impact of OCD on QoL. Nonetheless, the results of this paper do suggest a significant impact. Use of QoL measures in clinical settings will provide patients with an opportunity to express their concerns and assist clinicians to evaluate the effectiveness of management beyond the clinical outcomes. This paper also highlights the lack of a disease-specific QOL instrument and the importance of developing a validated measure to assess QOL in OCD, enabling comparison across countries and occupational groups.